Das historisch-philologische Vorgehen bei Aristoteles und in der Wissenschaft seiner Zeit: Einige Randbemerkungen - Pozdnev, Michael (Hyperboreus, 2021)
Proceeding from the emancipation of historical research marked by the scientiﬁc work of M. I. Rostovtzeﬀ the author makes a few side remarks on the text and cultural studies in the time of Aristotle, when the gap between philology and history has not yet occurred. The very existence of the then philology is a matter of dispute. It is true that intellectuals dealt in explicating Homeric texts since as early as the outgoing 6th c. BC: the term Ὁμηρικοί, conceivably hinting at Metrodorus of Lampsacus in Ar. Met. 1093 a 20–21, is actually the earliest term to stand for the profession of a philologist. However, the antiquarians of the 4th c. BC were hard at work collecting sources on literary history and interpreting texts beyond the Homeric epic. Hence the attempt to give the overall deﬁnition of literature which Aristotle undertakes in the ﬁrst chapters of the Poetics. This attempt was preceded by antiquarian research shared and inherited by disciples. Collecting was groundwork having goal in itself. The Proverbs of the Aristotelian catalogues, giving birth to paroemiology, were probably nothing more than a list of proverbs; the works of abstraction under the title On Proverbs are attested for Klearchos and Theophrastus. On Marvelous Things Heard is attributed to the school; a parallel with the Poetics shows that the earliest paradoxographic treatise was compiled directly from the esoteric works of Aristotle. With his Πυθιονῖκαι Aristotle “triumphed over Menaechmus of Sicyon” (Vita Hesychii). A patriot of his home city, Menaechmus evidently maintained a view that ﬁrst music competitions were set up in Sicyon. He dealt in etymologies, deriving ῥαψῳδοί from ῥάβδος in a rare meaning ‘verse’. At the end of ch. 3 of the Poetics, Aristotle discusses the origins of drama adducing, among other things, etymologies on which the Dorians are building their claims. An exotic etymology of -ῳδός allows to grasp an allusion to Menechmus, whom the author of the Poetics would not oppose openly. Collecting the didascaliae was evidently easier that proverbs: the records were kept by the archon, it only took some time to put them together in an orderly way. The political circumstances being propitious, the doors of the state archive were thrown wide open for Aristotle. Licurgus, likewise an attendee of the Plato’s Academia, saw to the production of an established text of the great trio in the revamped theatre of Dionysus. This famous edition was to be borrowed by Ptolemy III. It is common knowledge that the ὑποθέσεις of Byzantine MSS go back to the lists compiled by Aristotle. It is reasonable to conjecture that the standardized text of the tragedies made available to the Alexandrians was initially annotated by the same hand that compiled the Didascaliae and the Dionysiac victors. Legend has it that Alexander held a copy of Ilias ‘out of a casket’, and even commented on the Homeric text. It may be, in part, true, since it is evident that Aristotle used to read and discuss this text with his disciple. The penultimate chapter of the Poetics is fully devoted to the discussion of contended passages. In all probability, these sections were imported from – the Homeric problems. Zoilus, whose satirically naïve interpretations spiked the Homeric studies of the time, could well have been an adversary of Aristotle, while Glaucon of Theos counts as a proponent. Referring to Glaucon Aristotle articulates one of the plain truths of philological studies: understanding should precede criticism, or else the latter would turn against the one who voices it. His attitude as an interpreter is deﬁnitely apologetic. On the whole it is noticeable that the painful awareness of a gap between philology and history vexing the scholars for the last two centuries seems to have never occurred in the time of Aristotle. Following his thought, we observe an easy and natural, predetermined by the very object of research, unity of two types of argumentation. When dealing with an historical fact, such as, for instance, the origins and early history of drama, anthropological and historical causes have the lead, while discussing poetry argumentation ἀπὸ τῆς λέξεως prevails.